Immigration as a factor in American history - Handlin, Oscar 1915-2011 (Englewood Cliffs, New Jersey Prentice-Hall, 1959)
TRACES THE HISTORY OF IMMIGRANTS DESCRIBING PROBLEMS OF ADJUSTMENT AND HIS INDISPENSABLE ROLE IN THE INDUSTRY, AGRICULTURE, POLITICS, AND CULTURAL LIFE OF AMERICA.
The Dimensions of the Problem -- The Lessons of the Colonial Experience / William Rawle -- The Westward Flow of Peoples / Marcus L. Hansen -- Some Indications of Volume / Brown and Roucek -- Some Indications of Motive / Samuel Gompers -- The Old World Background -- The Flight from Famine in Ireland / Father John O'Sullivan, Lord Mountcashell -- Migration out of Germany / Chambers's Edinburgh Journal -- The Disruption of the East European Economy / Emily Greene Balch -- The Source of Italian Labor / John Foster Carr -- The Perils of the Crossing / Andreas Geyer, Robert Louis Stevenson -- The Economic Adjustment -- The Immigrant and American Agriculture / Marcus L. Hansen, Calvin Colton -- The Immigrant Artisan / S. H. Collins -- The Immigrant Buisnessman / Abraham Kohn -- The Immigrant and the Labor Market / United States Immigration Commission, Isaac A. Hourwich -- The Industries Manned by Immigrants / Hagerstown Torch-Light, John D. Warner, W. R. Jones, Peter Roberts -- The Immigrant and American Population / Francis A. Walker, Walter F. Willcox -- Immigrant Organization -- The Churches / Stuart -- Immigrant Organization for Self-Help / Massachusetts Commission of Immigration -- To Preserve the Old Culture / A. M. Skibinska, Mark Villchur, Mordicai Soltes -- The Immigrant in American Politics -- The Immigrant and the City Machine / Lincoln Steffens, George W. Plunkitt, Robert A. Woods -- Widening Visions of Politics / Carl Schurz, Alfred E. Smith -- American Politics and the Outer World / John Hay -- Cultural Contributions -- The European Scholar as Teacher / Palmer -- The European as an Impresario / Theodore Thomas -- An Immigrant Author / Lincoln Colcord -- Grace as an Aspect of Culture / Charles F. Read -- The Passionate Italian / Putnam's Monthly -- The Good-Natured German / Charles F. Adams -- Realism in the Yiddish Theater / Hutchins Hapgood -- Conceptions of Americanization -- America as a Melting Pot / Crevecoeur, Emma Lazarus, Israel Zangwil, Percy S. Grant -- Cultural Pluralism / Horace M. Kallen, Carl H. Grabo -- Advocates of Assimilation / Richmond Mayo-Smith -- The Immigrant Views His Own Adjustment / Polish Immigrant, A. R. Dugmore -- Restriction -- The Orientals and Color Predjudice / Mary R. Coolidge, Carey McWilliams -- Religious Intolerance / Oscar and Mary F. Handlin -- Racism / Madison Grant -- The Literacy Test Defended / Samuel Gompers -- The Literacy Test Condemned / Woodrow Wilson -- Effects of the War / Robert DeC. Ward -- The Quota System and Its Effects / William S. Bernard -- The Aftermath -- America: A Land of Immigrants / President's Commission on Immigration.
Keywords: Immigrants -- United States; United States -- Foreign population; United States -- Emigration and immigration